The Legal Nature of Independent Guarantees - Abbas, Shaymaa; Abdel Reda, Hussein (Journal of Legal Sciences, 2023)
The guarantee has been known since ancient times as the most widely used personal guarantee, whether at the commercial or civil business level, internally and externally. However, it suffered from weaknesses from the point of view of creditors. In search of a safer personal guarantee, and based on contractual freedom, independent guarantees arose, starting with practice, followed by the stage of legislative regulation.This type of new guarantees is based on the principle of independence. The independent guarantor, who is the debtor of the guarantee, is bound by a personal guarantee originating in the contract with the inability to adhere to defenses, which constitutes an advantage that tempts creditors, and the well-known legal systems cannot accommodate it, such as (Surtyship, Imperfect Representation, Stand-By Letter Of Credit).